The role of the MYL12A liquid-liquid phase separation in neutrophil improves the prognosis of acute respiratory distress syndrome: a multi-omics analysis - Guo, Yufang; Li, Longjie; Wang, Yongjun; Wang, Zexu; Qiu, Wei; Li, Qian; Wang, Li; Wan, Bing (Frontiers in Immunology, 2025)
BackgroundIn acute respiratory distress syndrome (ARDS), neutrophils, as the primary effector immune cells, undergo profound transcriptional and phenotypic reprogramming in response to complex inflammatory stimuli, modulating signal transduction and immune responses. Liquid-liquid phase separation (LLPS) plays a pivotal role in transcriptional dynamics and signal transduction, critically influencing gene expression stability. However, the mechanistic and clinical implications of LLPS in ARDS progression remain elusive.Materials and methodsThis study systematically characterized neutrophil LLPS in ARDS through integrated single-cell transcriptomes (GSE157789), proteomes (GSE32707/GSE76293), and clinical cohorts date. LLPS-associated genes (LCGs) were screened from the PhaSepDB 2.1 database and subsequently integrated with single-cell sequencing data from Gene Expression Omnibus (GEO) to quantify neutrophil LLPS scores and divide patient stratification into high and low LLPS groups for differential expression analysis of critical LCGs and associated pathways. Phase-separated droplets were then isolated from peripheral blood neutrophils of ARDS patients and N-formylmethionyl-leucyl-phenylalanine (fMLP) -stimulated neutrophils, followed by proteomic identification of droplet-associated proteins and candidate gene selection through GEO data analysis. The prognostic value of LLPS scores and candidate genes was subsequently validated in clinical cohorts, while the relationship between phase separation of candidate genes and cellular function was experimentally confirmed through immunofluorescence, Western blotting, and complementary functional assays.ResultsNeutrophils in ARDS exhibit elevated LLPS scores (p<0.05), with differentially expressed LCGs enriched in RhoA/ROCK-mediated cell polarization and migration pathways. Multi-omics integration identified MYL12A as a core phase-separation regulator, whose protein levels in phase-separated droplets positively correlated with oxygenation index (r=0.9536, p=0.0119) but inversely with SOFA scores (r=-0.8896, p=0.0433). Patients with high LLPS scores demonstrated significantly improved overall survival (p=0.046), suggesting a protective role of LLPS in ARDS pathogenesis. Mechanistically, the chemoattractant fMLP triggers reversible MYL12A phase separation via phosphorylation at Ser19, thereby potentiating neutrophil migratory capacity.ConclusionsThis study demonstrates that LLPS dynamically regulates neutrophil migration through MYL12A phosphorylation-dependent phase separation, exerting immunoprotective effect in ARDS. The LLPS status of MYL12A and its activity score may serve as ARDS prognostic biomarkers and offer a novel strategy for developing LLPS-targeted immunomodulatory therapies.